ANALYSIS OF MISCELLANEOUS STUDENTS' MISCONCEPTION ON TEMPERATURE AND HEAT MATERIALS USING THE CERTAINTY OF RESPONSE INDEX (CRI) METHOD - Putri, Clarisa Angelia; Awwalina, Roisa; Zahroh, Fatimatus; Maryamik, Siti; Hurin'in, Nabilah; Mukarromah, Zaitun; Mu'aziyah, Siti Eneng Sururiyatul; Putri, Suci Indah (Prodi Pendidikan IPA FMIPA Universitas Negeri Malang, 2025)
This study aims to analyze junior high school students' misconceptions related to temperature and heat material, and to improve the quality of learning through identifying concepts that are difficult to understand. The method used is descriptive qualitative with the Certainty of Response Index (CRI) approach to measure students' level of understanding. The research sample consisted of 108 7th grade students in Bangkalan district. The results showed that students experienced various misconceptions, especially on the concepts of temperature, heat, and heat transfer, with a significant frequency of misconceptions. These findings indicate the need for the application of more interactive and contextual learning methods, such as direct experiments and the use of visual illustrations, to improve students' understanding. The conclusion of this study emphasizes the importance of identifying misconceptions in designing effective teaching strategies, as well as the need for further research with larger samples and diverse methods to understand the factors that influence students' understanding. This study is expected to contribute to the development of curriculum and teaching methods in physics education, as well as help students understand the concepts of temperature and heat better, so that they can improve their learning achievement.